Estádio de desenvolvimento do milho. 3. Avaliação de silagens por intermédio de parâmetros de fermentação ruminal - Mendes Lavezzo, Otávia Elisa Nogueira [UNESP]; Lavezzo, Wagner [UNESP]; Wechsler, Francisco Stefano [UNESP] (My University, 1998)
The objective of this experiment was to analyze the rumen fermentation of silages made from corn harvested at milk stage (MS), milk early dough stage (MEDS), medium dough stage (MDS) and semi-hard dough stage (SHDS). Rumen fluid was collected from sheep by esophageal tube at 0, 1, 3 and 6 hours after feeding. There were no differences among silages for ammonia nitrogen (NH3-N) and methylene blue reduction time (MBRT). Only the MS and SHDS silages differed in rumen pH (6.82 and 6.53, respectively). Differences in total rumen VFA and acetic acid concentrations (mmoles/L) were observed among stages, but not between MS (36.40 and 22.13) and MEDS (42.49 and 25.73), nor between MDS (64.52 and 40.34 respectively) and SHDS (64.09 and 43.61, respectively). The periods of 1 and 3 hours after feeding showed the smallest pH values (6.47 and 6.63), the highest NH3-N concentrations (9.75 and 10.56 mg/dL) and the highest concentrations of total VFA, and acetic and propionic acids (60.33, 37.05 and 16.73; 59.40, 35.28 and 16.84 mmoles/L, respectively). On the whole, the MDS and SHDS silages showed the best rumen fermentation patterns based on pH and total and individual VFA values.
Corn development. 3. Silage evaluation by rumen fermentation parameters
Keywords: Corn silage; Maturity stage; Rumen fermentation; Sheep